Семь чудес и гробница теней - Леранжис Питер (Наследники Атлантиды, 2015)
Экземпляры: ф.2 (20231009) / Инвентарный номер: 64033 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: Л 49 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-445